Efsiensi Kinerja Rantai Pasok Gula Semut CV. Menoreh Politan Di Kabupaten Kulon Progo (Efficiency of CV Menoreh Politan Supply Chain Performance Of Coconut Sugar , Kulon Progo Regency) - Annisa Fajar Fadhilah (Journal of Food System & Agribusiness, 2017)
CV Menoreh Politan is one of sugar coconut companies in Kalibuko, Kokap, Kulon Progo Regency Yogyakarta. Some of its coconut sugar products are sent to various regions in Indonesia, and some others are occasionally exported. The company, however, had encountered some constraints both in supply and product fulfillment. This research was, Â therefore, aimed at studying the efficiency of performance at CV Menoreh Politan. The input variables used were order fulfillment cycle, supply chain flexibility, total supply chain cost, cash to cash cycle time, and daily inventory, while input variables for output of supply chain performance were delivery performance, order fulfillment, and conformity with standard. The efficiency of coconut sugar supply chain performance is analyzed by Data Envelopment Analysis (DEA) method with constant return to scale (CRS) assumption.Â  Analysis of farmer efficiency by using Data Envelopment Analysis (DEA) resulted in farmer efficiency level. CV Menoreh Politan has operated efficiently with its 14 partners (24.14 percent), while the remaining 44 farmers of CV Menoreh Politan (75.86 percent) have not reached the maximum efficiency level. The inefficiency of farmers was largely due to the cost of supply chains and long-term enterprise turnover. Overall, the collectors have been fully operational. Similarly, the company has been technically efficient, meaning that in terms of input and output, it has been good.